Evaluation of GeneXpert MTB/RIF for determination of rifampicin resistance among new tuberculosis cases in west and northwest Iran - Atashi, S. (New Microbes New Infect, 2017)
Despite a Mycobacterium tuberculosis control programme and anti-tuberculosis drugs, drug-resistant tuberculosis (DR-TB) is one of the most serious public health issues worldwide. Rapid laboratory diagnosis of M. tuberculosis is needed for the diagnosis of multidrug-resistant (MDR) TB and to find the optimal treatment protocol. The purpose of this study was to detect resistance to rifampicin in new cases of TB using the GeneXpert MTB/RIF (M. tuberculosis/rifampicin) assay and the standard proportional method in west and northwest Iran. In this descriptive cross-sectional study, sputum samples were enrolled and screened for M. tuberculosis using Ziehl–Neelsen stain and mycobacterial culture. Samples from individuals with smear-positive TB were cultured on Lowenstein–Jensen medium; afterwards, the presence of resistance to rifampicin was examined by the GeneXpert MTB/RIF and standard proportional methods. A total of 400 new cases of suspected TB were collected, 162 (40.5%) of which were smear- and culture-positive for M. tuberculosis. The frequencies of rifampicin resistance in new smear-positive TB cases were 3.1% and 4.3% for GeneXpert and standard proportional method, respectively. Sensitivity and specificity of GeneXpert were 71% and 100%, respectively, compared with the proportional method. GeneXpert can be a quick and helpful method for the diagnosis of rifampicin-resistant TB in regions with high rates of DR-TB or MDR-TB. GeneXpert MTB-RIF assay must be used as an early diagnostic method whose results must be confirmed by the standard proportional method. The GeneXpert and proportional methods complement but do not replace each other.